PERMASALAHAN TERKAIT PENGGUNAAN OBAT (DRUG RELATED PROBLEM) PADA PASIEN LANSIA DI NEGARA-NEGARA BERKEMBANG - Islami, Afif (Penerbit Lafadz Jaya, 2025)
The global geriatric population is rapidly increasing, particularly in developing countries, leading to higher burdens of chronic diseases and polypharmacy, which elevate drug-related problems (DRPs). This narrative review aims to comprehensively analyze DRPs among elderly patients in developing countries from 2015-2025, focusing on prevalence, risk factors, and interventions. Population comprised primary studies on geriatric patients (≥60 years) from Indonesia, India, Ethiopia, Vietnam, and Malaysia; purposive sample included 20 selected studies. Instruments involved systematic literature search protocols using keywords like